Das Ich und sein Gehirn Die Herausforderung der neurobiologischen Forschung für das (Straf-)Recht - Duttge, Gunnar (Universitätsverlag Göttingen, 2009)
In recent years, the debate about the free will has gained intensity. The phase of the heated debate has become a more pertinent and interdisciplinary. But still there are misunderstandings, misconceptions or ambiguities, which are sometimes accompanied by an attitude of denial discourse. This volume helps to highlight the self-perceptions and views of the concerned disciplines: Philosophy and Neuroscience, criminal science and criminal law practice, and not least the Forensic Psychiatry. The book does not claim to present definitive answers but provides clarifications that allow the interested reader to form an reflected opinion. The contributions have come from the first workshop of the Institute of Criminal Sciences at the Georg-August-Universität Göttingen in 2007.